Edoxaban for treatment of venous thromboembolism in patient groups with different types of cancer: Results from the Hokusai VTE Cancer study. Issue 185 (January 2020) - Mulder, F.I.; van Es, N.; Kraaijpoel, N.; Di Nisio, M.; Carrier, M.; Duggal, A.; Gaddh, M.; Garcia, D.; Grosso, M.A.; Kakkar, A.K.; Mercuri, M.F.; Middeldorp, S.; et al.
Abstract: Background: The safety and efficacy of edoxaban and dalteparin is unclear for several cancer groups. Methods: We evaluated the occurrence of the primary outcome in large cancer groups. The primary outcome was the composite of recurrent VTE or major bleeding over 12 months. Results: In patients with gastrointestinal cancer, the primary outcome occurred in 19.4% patients given edoxaban and in 15.0% given dalteparin (risk difference [RD], 4.4%; 95%-CI, −4.1% to 12.8%). The corresponding rates for edoxaban and dalteparin were 10.4% and 10.7% for lung cancer (RD, −0.3%; 95%-CI, −10.0% to 9.5%), 13.6% and 12.5% for urogenital cancer (RD, 1.1; 95%-CI, −10.1–12.4), 3.1% and 11.7% for breast cancer (RD, −8.6; 95%-CI, −19.3–2.2), 8.9% and 10.9% for hematological malignancies (RD, −2.0; 95%-CI, −13.1–9.1), and 10.4% and 17.4% for gynecological cancer (RD, −7.0; 95%-CI, −19.8–5.7). In the subgroup of gastrointestinal cancer, edoxaban was associated with a 3.5% lower absolute risk of recurrent VTE and a 7.9% higher risk of major bleeding. Conclusion: Edoxaban has a similar risk-benefit ratio to dalteparin in most cancer groups. In those with gastrointestinal cancer, the lower risk of recurrent VTE and the advantages of oral therapy need to be balanced against the increased risk of major bleeding. Highlights: The Hokusai VTE Cancer Study was a randomized controlled trial for cancer patients. It randomized patients to either edoxaban or dalteparin for the treatment of VTE. This analysis provides adjudicated study outcomes for all large cancer groups. In most cancers, the primary outcome was comparable between both regimens. The major bleeding risk in gastrointestinal cancer is higher in edoxaban recipients.